On the selection effects in catalogues of binary stars - Isaeva, A.A. (Advances in Astronomy and Space Physics, 2012)
Investigation of physical properties of different kinds of binary stars can provide us with an invaluable information about star formation and evolution. To obtain present-day distributions of binaries along various parameters from catalogues, selection effects should be taken into account. In this paper some catalogues of visual binaries were investigated with respect to selection effects. The distributions of catalogue binaries with respect to components separation, limiting magnitude and magnitude difference were studied and corrected for selection effects.